Estimation and characterization of flood disaster waste from residential areas of Taytay - Bartolome, Charlene T.; Aquino, Diocel Harold M.; Tanchuling, Maria Antonia N. (Quezon City College of Engineering, University of the Philippines Diliman, 2014)
The Philippines has a fair share of disasters due to its geographical location. These disasters, depending on its type and severity, produce massive amount of wastes that could overwhelm existing solid waste management facilities. There is a need to estimate and characterize disaster wastes because poor management of these wastes could lead to slow and costly recovery. This could also pose risk to human and environmental health. For this study, historical data for a 100-year flood was obtained from field surveys. Correlation between generated disaster wastes with experienced flood levels was also done. Finally, an estimate of the total disaster waste generated for the entire municipality for Taytay was obtained. The estimated total waste generated for the entire municipality was computed to be 19,622 m³. The percent composition of cloth, electronics, metal, paper, plastic and wood was computed to be 25.86%, 55.76%, 0.51%, 0.01%, 1.38% and 16.47% respectively.
Thesis (B.S. Civil Engineering)--University of the Philippines Diliman
Keywords: Floods; Refuse and refuse disposal